2005
DOI: 10.1016/j.jcv.2005.01.007
|View full text |Cite
|
Sign up to set email alerts
|

A phage-displayed cyclic peptide that interacts tightly with the immunodominant region of hepatitis B surface antigen

Abstract: The surface antigen (HBsAg) of hepatitis B virus (HBV) is highly conformational and generally evokes protective humoral immune response in human. A disulfide constrained random heptapeptide library displayed on the coat protein III of filamentous bacteriophage M13 was employed to select specific ligands that interact with HBsAg subtype ad. Fusion phages carrying the amino acid sequence ETGAKPH and other related sequences were isolated. The binding site of peptide ETGAKPH was located on the immunodominant regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…For example, phages decorated with peptides isolated from phage display have been used in ELISAs for the detection of anthrax spores 383 and the surface antigen of HBV. 384 For an alternative to the presentation of peptides on viruses, antibodies can also be presented on the viral scaffold for multivalent detection, and the previous section discussed how phage display and genetic engineering could be used for the display of antibodies and fragments thereof. As another approach, it was recently demonstrated that functionalization of PVX-based nanoparticles with protein A fragments can be used to display whole antibody molecules by using protein A's property of binding to the Fc region of the heavy chain of IgGs.…”
Section: Applications Of Virus-based Particlesmentioning
confidence: 99%
“…For example, phages decorated with peptides isolated from phage display have been used in ELISAs for the detection of anthrax spores 383 and the surface antigen of HBV. 384 For an alternative to the presentation of peptides on viruses, antibodies can also be presented on the viral scaffold for multivalent detection, and the previous section discussed how phage display and genetic engineering could be used for the display of antibodies and fragments thereof. As another approach, it was recently demonstrated that functionalization of PVX-based nanoparticles with protein A fragments can be used to display whole antibody molecules by using protein A's property of binding to the Fc region of the heavy chain of IgGs.…”
Section: Applications Of Virus-based Particlesmentioning
confidence: 99%
“…This suggests that C4 phage is most likely interacted with the immunodominant region of HBcAg. The negative control using an unrelated peptide with the sequence ETGAKPH that binds tightly to HBsAg (ad subtype) (Tan et al, 2005) did not inhibit the binding of the C4 phage to HBcAg.…”
Section: Phage-peptide Inhibition Assaymentioning
confidence: 98%
“…ABTS was added and A 405 deter- mined. The nucleotide sequence of the insert was determined as described in Tan et al (2005) …”
Section: Biopanningmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is considered to be antigenically most significant from a vaccine development point of view [5][6][7]. In addition, HBsAg are also needed to develop sensitive and specific immunoassays for in vitro diagnosis of anti-HBs antibodies as capture agents and reference markers [8,9]. Recombinant HBsAg has been successfully produced from the Pichia pastoris expression system and its advantages have been vastly reviewed in the literature [10][11][12].…”
Section: Introductionmentioning
confidence: 99%